2008
DOI: 10.1080/13682820701489717
|View full text |Cite
|
Sign up to set email alerts
|

Mapping practice onto theory: the speech and language practitioner's construction of receptive language impairment

Abstract: While theories of the deficit dominate the literature they appear to play a relatively small part in the eclectic practice of speech and language therapists. Theories of therapy may develop relatively independent of theories of deficit. While this may not present a problem for the practitioner, whose principal focus is remediation, it may present a problem for the researcher developing intervention efficacy studies, where the theory of the deficit will need to be well-defined in order to describe both the subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…However, they referred to evidence from their own experience, from local evaluations as well as published research. Furthermore, the level of evidence was only one of the factors that was taken into account when selecting interventions and respondents were clearly balancing practical issues with a process of selecting an intervention to match the needs of the children, perhaps using what Law et al ( 2007) referred to as 'theories of therapy'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they referred to evidence from their own experience, from local evaluations as well as published research. Furthermore, the level of evidence was only one of the factors that was taken into account when selecting interventions and respondents were clearly balancing practical issues with a process of selecting an intervention to match the needs of the children, perhaps using what Law et al ( 2007) referred to as 'theories of therapy'.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies of practice have surveyed speech and language therapist's (SLTs) use of interventions for children with speech problems (McLeod & Baker, 2004;Joffe & Pring, 2008) and receptive language impairment (Law, Campbell, Roulstone, Adams & Boyle, 2007). The two studies of speech interventions focused on interventions already mentioned in the research literature.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which professional practice with children with RELI maps on to underlying theory has been investigated in a recent survey of qualified SLTs in the UK, focusing on practice with children aged 5 to 11 years 69 . The findings revealed that children with RELI are seen as a priority and receive extensive services that reflect diverse practice.…”
Section: Interventions For Relimentioning
confidence: 99%
“…In an analysis of the therapy rationales of experienced paediatric SLTs, tacit categorization of therapy tasks as either metacognitive or skills acquisition was revealed (Law et al . ). Tasks to develop explicit language skills were considered as skills acquisition, while those aimed at improving the child's ability to reflect on the process of learning about language were metacognitive.…”
Section: Introductionmentioning
confidence: 97%